Technology, Aging and Home and Community Care: Picking the Right Problems to Solve - James Shaw, Sonia Nizzer and Sandra McKay (HealthcarePapers, 2024)
As the Canadian population ages, the imperative to support aging in the community grows increasingly urgent. In this commentary, we build on Kokorelias et al.'s (2024) article to address the ethically appropriate role of digital technologies in supporting aging at home. We argue that a nuanced perspective on this topic is crucial. Focusing on the pivotal role of personal support workers in home and community care, we highlight the multiple challenges they face, from precarious employment to safety concerns. While digital innovations offer promise, we suggest that a holistic approach blending policy initiatives with technological advancements is imperative.
Keywords: home care, aging, digital health, techno-solutionism, personal support workers